Fast Charge Separation by Direct Combination of Fullerene C60 with ZnO Quantum Dots and its Application in Ultraviolet Photodetectors - Park, Jinseo; Shim, Jaeho; Son, Dong Ick (Institute of Electrical and Electronics Engineers, 2025)
The charge separation ability of zinc oxide (ZnO)-fullerene (C-60) quantum dots (QDs) was analyzed and ultraviolet photodetectors were fabricated using spin-coating methods. The structural properties of the ZnO-C-60 core-shell QDs and poly-N-vinylcarbazole (PVK) polymer composites were analyzed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Optical characterization studies revealed that the ZnO-C-60 core-shell QDs exhibit a higher quenching effect ratio (97.72%) in the ultraviolet region and higher F & ouml;rster resonance energy transfer efficiency (89%) from direct conjugation with the ZnO core to the C-60 shell. The photodetectors based on ZnO-C-60 core-shell QDs generated photocurrent of 4.92 mu A under an external bias of 1 V at a wavelength of 365, and the photo-responsivity was 1.51 A/W. The photo-reaction mechanism is explained through energy diagrams based on experimental results.